2019
DOI: 10.1101/666982
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Phylogeographic reconstruction using air transportation data and its application to the 2009 H1N1 influenza A pandemic

Abstract: Influenza A viruses cause seasonal epidemics and occasional pandemics in the human population. While the worldwide circulation of seasonal influenza is at least partly understood, the exact migration patterns between countries, states or cities are not well studied. Here, we use the Sankoff algorithm for parsimonious phylogeographic reconstruction together with effective distances based on a worldwide air transportation network. By first simulating geographic spread and then phylogenetic trees and genetic sequ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…These findings likely reflect the increased genetic differentiation of SARS-CoV-2 genomes due to the ongoing accumulation of mutations as well as reduced international travel due to travel restrictions and lockdown measures. The resolution and accuracy of phylodynamic and phylogeographic analyses [Kühnert et al 2016, Lemey et al 2020, Reimering et al 2020] will likely benefit from this increased geographical localization of individual SARS-CoV-2 viral variants. Selective sweeps of viral types with increased transmissibility [Rambaut et al 2020], however, may counteract the observed trend of increasing geographical localization by reducing global SARS-CoV-2 genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…These findings likely reflect the increased genetic differentiation of SARS-CoV-2 genomes due to the ongoing accumulation of mutations as well as reduced international travel due to travel restrictions and lockdown measures. The resolution and accuracy of phylodynamic and phylogeographic analyses [Kühnert et al 2016, Lemey et al 2020, Reimering et al 2020] will likely benefit from this increased geographical localization of individual SARS-CoV-2 viral variants. Selective sweeps of viral types with increased transmissibility [Rambaut et al 2020], however, may counteract the observed trend of increasing geographical localization by reducing global SARS-CoV-2 genetic diversity.…”
Section: Discussionmentioning
confidence: 99%
“…It is also key for genomic epidemiology, i.e. tracing viral spread using genomic information 71,72 and genome-based viral phenotyping 73 . Strains can differ in their phenotypes, such as virulence, resistance, or the degree of their immune resistance to host immunity, which may be critical for the choice of therapy.…”
Section: Discussionmentioning
confidence: 99%